2022
DOI: 10.3390/ijms23179678
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanoflowers of MgFe2O4, Bentonite and B-,P- Co-Doped Graphene Oxide as Adsorbent and Photocatalyst: Optimization of Parameters by Box–Behnken Methodology

Abstract: In the present study, nanocomposites having hierarchical nanoflowers (HNFs) -like morphology were synthesized by ultra-sonication approach. HNFs were ternary composite of MgFe2O4 and bentonite with boron-, phosphorous- co-doped graphene oxide (BPGO). The HNFs were fully characterized using different analytical tools viz. X-ray photoelectron spectroscopy, scanning electron microscopy, energy dispersion spectroscopy, transmission electron microscopy, X-ray diffraction, vibrating sample magnetometry and Mössbauer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…However, the potential of +2.38 eV and +2.72 eV for OH − to ·OH and H 2 O to ·OH were higher than that of the photocatalysts. The band alignments versus the normal hydrogen electrode (NHE) were indicated in Figure 6 e. The possible formation procedure of ·OH was attributed to the O 2 due to the potential energy of +0.695 eV for O 2 to H 2 O 2 , which subsequently was transformed to ·OH with the capture of electrons [ 51 , 52 ]. The results showed reactive species in this photocatalytic system including O 2 − , H+, and ·OH, which coincided with the ESR of the photocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…However, the potential of +2.38 eV and +2.72 eV for OH − to ·OH and H 2 O to ·OH were higher than that of the photocatalysts. The band alignments versus the normal hydrogen electrode (NHE) were indicated in Figure 6 e. The possible formation procedure of ·OH was attributed to the O 2 due to the potential energy of +0.695 eV for O 2 to H 2 O 2 , which subsequently was transformed to ·OH with the capture of electrons [ 51 , 52 ]. The results showed reactive species in this photocatalytic system including O 2 − , H+, and ·OH, which coincided with the ESR of the photocatalysts.…”
Section: Resultsmentioning
confidence: 99%
“…XPS spectra of Fe 2p of samples before and after CO pretreatment are presented in Figure 6 . The peaks at 710.97 and 724.45 eV are assigned to Fe 2p 3/2 and Fe 2p 1/2 , respectively, and the satellite peak at 719.16 eV is attributed to Fe 2 O 3 [ 36 , 37 ]. No peaks assigned to Fe 0 and Fe 2+ were detected, as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found when the hierarchical nanoflowers of the MgFe 2 O 4 , Bentonite and B-, Pco-doped Graphene Oxide were tested for their reusability and stability. The degradation efficiency was found to be decreased by only 5% after 5 consecutive cycles [83].…”
Section: Reusability and Stabilitymentioning
confidence: 95%
“…Hierarchical nanoflowers of MgFe 2 O 4 , bentonite and boron, phosphorous co-doped graphene oxide synthesized using the ultrasonication method showed that chiffon-like co-doped graphene oxide nanosheets were wrapped on the MgFe 2 O 4 -bentonite surface, resulting in a porous flower-like morphology. The excellent conductivity of the co-doped nanosheets allowed for a quick charge carrier transport, which aided in the separation of those carriers during the photocatalytic reaction [83]. Cationic surfactant cetyltrimethyl ammonium bromide was chosen to coat the MgFe 2 O 4 because its negatively charged surface can interact with the surfactant during ultrasonication [84].…”
Section: Methods Of Synthesis Of Ferrites and Their Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation